PENGARUH KUALITAS PELAYANAN TERHADAP KOLEKTIBILITAS PEMBIAYAAN MURABAHAH PADA BANK SYARIAH MANDIRI CABANG KAMPUNG BARU MEDAN - Fatmawarni, - (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
The Effect of Service Quality to Murabahah Cost at Syariah Mandiri Bank Kampung Baru Branch Office Medan. The objective of this research is to evaluate the service quality point of tangible dimension, empathy, reliability, responsiveness, assurance to murabahah collectibles cost of Syariah Mandiri Bank stimulatingly and partially. The hypothesis of this research was formulated that there was effect of service quality significantly as well as tangible dimension, empathy, reliability, responsiveness, and assurance to murabahah collectibles cost of Syariah Mandiri Bank at Kampung Baru Branch Office Medan stimulatingly and partially in other word receive the alternative hypothesis (Ha) and reject Nol Hypothesis (Ho) with condition if probability score F is (Sig) alpha 0, 05. The method of this research was applied correlation research method, and data analysis quantitatively with using parametric statistic analysis. The population which became the object of the research was Syariah Mandiri Bank customers of Kampung Baru Branch Office with using murahabah cost facilities. Sampling had done on 35 respondents with accidental technique. Research findings that there is significant effect tangible dimension, empathy, reliability, responsiveness and assurance on murabahah collectibles cost of Syariah Mandiri Bank Kampung Baru Branch Office.